An analysis of the demand and uptake of agricultural insurance in developing countries - Dissanayake Mudiyanselage Madusha Sandeepani; Pathiraja Nishanthage Malsha Madushani Wijerathna; Kodikarage Nirosha Nadeeshani Silva (Agricultural Economics Research Review, 2023)
Climate change, natural risks, and market price fluctuations impact agricultural production and farm income. The risks can be smoothened by using concepts from insurance, but numerous challenges constrain the demand and uptake of agricultural insurance products. We review the products in developing countries for insights into formulating an agricultural insurance scheme for Sri Lanka and we find a range of products that have potential. The government and policymakers can use our findings to develop and implement an agricultural insurance scheme in Sri Lanka that serves as a risk management tool.